The gift of health: Cuban medical cooperation in Kiribati - Werle C; McLennan S; Leslie H (Massey University, 2023)
Since 2006, 33 I-Kiribati students have undertaken medical education in Cuba and returned home as doctors, but little is known about how they translate the Cuban preventive model of care to medical practice in the Pacific context. The research addresses this gap through qualitative fieldwork in South Tarawa and reveals that the assimilation of Cuban-trained doctors into medical practice is complicated by challenges related to clinical skills, language and contextual knowledge. These challenges have been successfully addressed with the development of the Kiribati Internship Training Programme but a misalignment between the prevention-focussed medicine taught in Cuba, and the curative orientation of the Kiribati health system and internship programme remains a concern, and the graduates’ knowledge and experience of primary and preventative care is not yet well utilised. This paper argues that the challenge now is to ensure that the knowledge and skills gained by the Cuban graduates at all steps of this journey are utilised in order to bring better health outcomes for the people of Kiribati.
Keywords: Kiribati; Cuba; Pacific health; medical education; Cuban medical cooperation